Muscular Fitness and Work Ability among Physical Therapists - Ezzatvar, Yasmín (Int J Environ Res Public Health, 2021)
The Work Ability Index (WAI) is a validated and widely used tool in occupational research. However, normative values for physical therapists (PTs) by age and sex are lacking. Although the nature of PTs’ work is physically demanding, it is unknown whether muscular fitness is associated with their WAI. This study sought to provide reference WAI data for Spanish PTs and to evaluate the association between PTs’ muscular fitness and WAI. Data on WAI of 1005 PTs were collected using a questionnaire. A subgroup (n = 68) performed a battery of physical tests including grip strength, push-ups and back-extension endurance. Associations between muscular fitness and WAI were evaluated using logistic regression controlling for various confounders. PTs aged 50 years or older had lower WAI scores than their younger counterparts. PTs with high back-extension endurance scored 3.5 (95% CI) higher in the WAI than those with low endurance. No associations were found between grip strength or number of push-ups and WAI. Our findings seem to highlight the importance of muscular fitness in PTs, especially the back-extension endurance.